A Study the Way of Life According to Principles of Sappurisdhamma 7 in the Epidemic Sitution of the Coronavirus (Covid-19) of the Village Health Volunteer Pakchom District Loei Province - Samacitto (Wattanapanson), Phra Surachet; ., Phrarachapreecharmunee; Pariyasuwat, Jarrukit (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were 1) to study the ways of life in preventing COVID-19 by VHVS, 2) to study the way of life according to the 7 Sappurisadhamma in the situation of the COVID-19 epidemic of VHVS,And 3) Propose guidelines for living according to the 7 Sappurisadhamma in the situation of the COVID-19 epidemic of Huai Bor Suen sub-district village health volunteers. It is an integrated research method. The sample group consisted of 114 VHVS, and 18 key informants using purposive random sampling. Research tools namely, a questionnaire with confidence values of both 0.846 and 0.878 and an interview form Data were analyzed with statistics, percentage, mean, and standard deviation. Pearson correlation coefficient and uses content analysis methods The results of the research revealed that 1) the way of life for COVID-19 prevention of the VHVS, overall and each aspect was at a high level. Knowledge has the highest average. 2) Living according to the Sappurisadhamma 7 during the COVID-19 epidemic of the VHVs overall and each aspect was at a high average level. Knowledge according to the principle of Sappurisadhamma 7 had the highest average and 3) Guidelines for living according to the 7 Sappurisadhamma during the COVID-19 epidemic of VHVs were summarized from the interviews as follows: (1) VHVs should be knowledgeable people. Have the ability to prepare information Know how to exercise judgment in the community. (2) Volunteers should be disciplined. Able to control their own emotions and behavior in a pattern know and understand the differences of people The results of the statistical hypothesis testing found that the relationship between the Sappurisadhamma 7 and the KAP Theory was positive and the same direction at a moderate level with an r value of 0.676 and a Sig value of 0.00.